2014
DOI: 10.1111/obr.12174
|View full text |Cite
|
Sign up to set email alerts
|

Processed foods and the nutrition transition: evidence from Asia

Abstract: This paper elucidates the role of processed foods and beverages in the 'nutrition transition' underway in Asia. Processed foods tend to be high in nutrients associated with obesity and diet-related non-communicable diseases: refined sugar, salt, saturated and trans-fats. This paper identifies the most significant 'product vectors' for these nutrients and describes changes in their consumption in a selection of Asian countries. Sugar, salt and fat consumption from processed foods has plateaued in high-income co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
218
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(234 citation statements)
references
References 57 publications
6
218
1
9
Order By: Relevance
“…However, these studies have been mainly conducted in already developed economies and even there the evidence remains somewhat contradictory (White, 2007). The largest comparative economic advantage for supermarkets and international food retail is in supplying processed, energy dense foods associated with adverse impacts on diets in developing countries (Baker and Friel, 2014;Hawkes, 2008). This is particularly relevant in developing country settings where procurement systems for fresh foods are still primarily traditional.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies have been mainly conducted in already developed economies and even there the evidence remains somewhat contradictory (White, 2007). The largest comparative economic advantage for supermarkets and international food retail is in supplying processed, energy dense foods associated with adverse impacts on diets in developing countries (Baker and Friel, 2014;Hawkes, 2008). This is particularly relevant in developing country settings where procurement systems for fresh foods are still primarily traditional.…”
Section: Introductionmentioning
confidence: 99%
“…So consumption of instant foods (particularly instant noodles), snack foods (such as potato chips), soft drinks and sweet cakes and bread products are all rising (Aekplakorn, 2011). When examined overall it has recently been shown that sugar sweetened beverages lead the way in Thailand for transitional caloric excess (Baker and Friel, 2014). As well, an increasing amount of food is being consumed outside the home or from restaurants and this food is often higher in fats, oils, sugar and salt than home cooked foods (Kosulwat, 2002).…”
mentioning
confidence: 99%
“…Of concern, soft drink consumption volumes are increasing in almost all countries. Thailand, Indonesia and the Philippines appear to have volumes comparable to those of H-ICs [66].…”
Section: The Rise Of Ncds and Risk Commodity Consumption Patterns In mentioning
confidence: 93%
“…Countries are also at varying stages of 'nutrition transition', a dietary-shift from traditional diets rich in staple foods and vegetables towards less healthy diets high in ultra-processed foods such as biscuits, confectionary, savoury snacks, processed meats and soft drinks [60][61][62][63][64][65][66]. As ultra-processed foods tend to be higher in sugar, salt, saturated and trans-fats relative to unprocessed or minimally processed foods, such dietary transitions are associated with rising rates of obesity and NCDs globally [13,21,65,[67][68][69][70].…”
Section: The Rise Of Ncds and Risk Commodity Consumption Patterns In mentioning
confidence: 99%
“…Health authorities recommend exclusive breastfeeding to six months and continued breastfeeding to two years and beyond (WHO/UNICEF 2003). There is significant evidence that China's modernisation has been accompanied by a dramatic decline in optimal infant and young child feeding (Hou 2014), a boom in consumption of ultra-processed and fast food (Baker and Friel 2014) including milk formula (Baker et al 2016) and an unprecedented epidemic of chronic disease and obesity and emerging health cost burdens (Popkin 2008). …”
mentioning
confidence: 99%